Policy on the application of conditional early release in Poland for the years 2014–2023 - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Conditional early release from the remainder of a prison sentence is a key institution in the regulation of the penitentiary population. The subject of this study is an analysis of the policy on the use of conditional early release from the remainder of the prison sentence between 2014 and 2023. The title institution has been assessed from the perspective of the number of convicts serving custodial sentences, the initiative of the bodies entitled to submit applications on this subject, and changes in the number of successful and unsuccessful applications. The analysis confirmed a clear decrease not only in the number of successful applications, but also in the interest of convicts in the title institution itself. It can be assumed that this is due to the nature of the penal and penitentiary policies implemented in recent years, i.e., the actual tightening of the repressive and isolation functions of imprisonment. This observation is confirmed by the numerous amendments to the penal codification tightening, inter alia, the grounds for applying for conditional early release from the remainder of the prison sentence.
Keywords: conditional release; custodial sentence; penal policy; convict; prison governor; prison population